AB INITIO STUDY ON REACTION MECHANISM OF UNDEC-10-EN-1-OL CARBONYLATIVE POLYMERIZATION WITH COBALT BASED CATALYSTS - (NIM : 20511006); Tim Pembimbing : Tim Pembimbing : Muhamad Abdulkadir Martoprawiro, Ph.D; D, ARIFIN
Carbonylative polymerization of undec-10-en-1-ol using cobalt complex as the catalyst to produce aliphatic polyester has been investigated at the B3LYP density functional level of theory. The proposed mechanism consisted of five reaction steps, i.e., the formation of active catalyst HCo(CO)3, coordination of olefin part of undec-10-en-1-ol, insertion of unde-10-en-1-ol to Co-H bond, carbonylation, and esterification. It was found that electronic energy of HCo(CO)3 + CO was much higher than the energy of HCo(CO)4. The most stable conformation of undec-10- en-1-ol coordinated-cobalt is the one with the olefin part which is parallel to the equatorial plane. There are 2 possible orientations of olefin coordination prior to olefin insertion into Co-H: olefin part of undecenol that is perpendicular to equatorial plane and the alkyl group in alkene that is (i) located at the same side as the Co-H bond (Co-syn) or (ii) at the opposite side from Co-H (Co-anti). The one with the Co-syn orientation has higher energy of 18.14 kJ mol-1 compared to the one with parallel orientation of undecenol towards the equatorial plane. Undec-10-en- 1-ol insertion to Co-H bond led to the Co- - -H-C agostic interaction between Co and beta-H, that was more stable than Co-syn complex (32.66 kJ mol-1). CO addition to alkyl cobalt tricarbonyl complex resulted in a five coordination complex with the alkyl at the axial position. Alkyl migration to CO in equatorial position generated an acyl complex with agostic interaction between Co and alpha-H of carbonyl. Rearrangement of the complex provided a more stable complex with agostic interaction between Co and oxygen from C=O group (15.98 kJ mol-1) and this conformation made an active carbonyl group to be ready for esterification. The esterification was accompanied by the dehydrogenation from alcohol group to produce an ester and regenerate back the active catalyst HCo(CO)3. Rate determining step for this mechanism was observed to be the formation of HCo(CO)3 from HCo(CO)4. HCo(CO)4 was the most readily complex to do CO dissociation.